2018
DOI: 10.1371/journal.pone.0198403
|View full text |Cite
|
Sign up to set email alerts
|

Tongxinluo attenuates reperfusion injury in diabetic hearts by angiopoietin-like 4-mediated protection of endothelial barrier integrity via PPAR-α pathway

Abstract: ObjectiveEndothelial barrier function in the onset and Tongxinluo (TXL) protection of myocardial ischemia/reperfusion (I/R) injury, and TXL can induce the secretion of Angiopoietin-like 4 (Angptl4) in human cardiac microvascular endothelial cells during hypoxia/reoxygenation. We intend to demonstrate whether TXL can attenuate myocardial I/R injury in diabetes, characterized with microvascular endothelial barrier disruption, by induction of Angptl4-mediated protection of endothelial barrier integrity.Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…ANGPTL4 is the target of peroxisome proliferator-activated receptors (PPAR) and induced by PPARα in mice and rat models [ 16 , 17 , 18 ]. Muscle-derived ANGPTL4 is induced by fatty acids via PPARδ, but not PPARα, and PPARγ in human skeletal muscle myotubes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…ANGPTL4 is the target of peroxisome proliferator-activated receptors (PPAR) and induced by PPARα in mice and rat models [ 16 , 17 , 18 ]. Muscle-derived ANGPTL4 is induced by fatty acids via PPARδ, but not PPARα, and PPARγ in human skeletal muscle myotubes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Composed of Radix ginseng, Buthus martensi, Hirudo, Eupolyphaga seu steleophaga, Scolopendra subspinipes, Periostracum cicadae, Radix paeoniae rubra, Semen ziziphi spinosae, Lignum dalbergiae odoriferae, Lignum santali albi, and Borneolum syntheticum, traditional Chinese medicine Tongxinluo (TXL) was registered in China Food and Drug Administration for the angina pectoris treatment in 1996. Recent researches demonstrated that TXL could protect the myocardium from I/R-injury, reducing the size of myocardial necrosis and no-reflow, and improving the cardiac performance in both non-diabetic [ 7 ] and diabetic [ 8 ] conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The protection mechanisms of TXL involved the protection of microvascular endothelial integrity by upregulating VE-cadherin, β-catenin, γ-catenin, JAM-A and integrin-α5 and subsequent reduction of myocardial hemorrhage, inflammation, oxidization, edema, apoptosis and necrosis, while eNOS inhibitor Nω-Nitro-L-arginine, peroxisome proliferator activated receptor-α (PPAR-α) inhibitor MK886 or small interfering RNA (siRNA) against angiopoietin-like 4 (Angptl4) partly canceled these effects of TXL, indicating that endothelial barrier function and PPAR-α/Angptl4 pathway played a key role in the protection of TXL against myocardial I/R-injury. [ 7 11 ] Several signaling pathways have been implicated in this protective role of TXL, including PKA/eNOS, [ 7 ] MEK/ERK, [ 12 ] and PPAR-α/Angptl4 [ 8 ] pathways.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations